(untitled) (Global Journal of Medical Research, 2020)
This work carried out to detect dipterous fly agents of Myiasis of domestic animals in Iraq during the year 2017. Seventy cases of Myiasis were determined in the domestic animals distributed in five provinces: Baghdad, Diyala, Wasit, Diwaniya and Basrah. Fifty one cases were wound Myiasis, and 19 were various Myiasis cases for aural five rectal, four urogenita, three ophthalmic and one oral. Four species of dipterous flies larvae: Chrysomya bezziana, Chrysomya megacephala, Lucilia sericata, Chrysomya albiceps were identified as Myiasis agents. Chrysomyabezziana was most prevalent species has been recording 50 injured, 27 of them injured in sheep. The larvae were collected from six species of domestic animals; sheep were more susceptible to Myiasis followed by cattle, dog, goat, buffalo and cat.